2016
DOI: 10.1002/jcph.832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Evolocumab (AMG 145), a Fully Human Anti‐PCSK9 IgG2 Monoclonal Antibody, in Subjects With Hepatic Impairment

Abstract: Evolocumab binds PCSK9, increasing low‐density lipoprotein cholesterol (LDL‐C) receptors and lowering LDL‐C. Target‐mediated evolocumab elimination is attributable to PCSK9 binding. As circulating PCSK9 and LDL‐C levels are primarily regulated by the liver, we compared evolocumab pharmacokinetics, pharmacodynamics, and safety in individuals with and without hepatic impairment. An open‐label, parallel‐group study evaluated the pharmacokinetics of evolocumab in hepatic‐impaired (Child‐Pugh Class A or B) or healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
4
26
1
Order By: Relevance
“…14,15 In this study, evolocumab effectively lowered LDL-C levels in patients with severe RI or ESRD receiving hemodialysis; the magnitude and timing of LDL-C lowering were consistent with those reported recently in a hepatic impairment study 16 and in other evolocumab clinical trials. Mean baseline serum PCSK9 levels and the time course of PCSK9 lowering by evolocumab were similar in the normal renal function and renally impaired groups, indicating that target-mediated clearance of evolocumab is not affected by impaired renal function.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…14,15 In this study, evolocumab effectively lowered LDL-C levels in patients with severe RI or ESRD receiving hemodialysis; the magnitude and timing of LDL-C lowering were consistent with those reported recently in a hepatic impairment study 16 and in other evolocumab clinical trials. Mean baseline serum PCSK9 levels and the time course of PCSK9 lowering by evolocumab were similar in the normal renal function and renally impaired groups, indicating that target-mediated clearance of evolocumab is not affected by impaired renal function.…”
Section: Discussionsupporting
confidence: 89%
“…Patients with severe RI and ESRD had geometric mean C max and AUC last that were within 37% of patients with normal renal function with no adjustment for body weight and within 26% after adjustment for body weight. 4,9 AUC last , area under the drug concentration-time curve from time zero to time of last quantifiable concentration; AUC inf , area under the drug concentration-time curve from zero to infinity; C max , maximum observed drug concentration; ESRD, end-stage renal disease; Q, quartile; SD, standard deviation; t max , time to reach C max . Of note, least-squares geometric mean evolocumab exposure values in patients with normal renal function were higher than recently reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, anti‐PCSK9 antibodies are proteins and are therefore not expected to be metabolised by the liver or kidneys; hence, no effects on the liver or kidneys are expected. For evolocumab, a small pharmacokinetics study reported no differences in efficacy or safety between healthy volunteers and in patients with mild or moderate hepatic impairment . Another evolocumab study reported no differences in LDL‐C lowering or safety among patients with normal renal function and those with severe renal impairment or end‐stage renal disease .…”
Section: Resultsmentioning
confidence: 99%
“…For evolocumab, a small pharmacokinetics study reported no differences in efficacy or safety between healthy volunteers and in patients with mild or moderate hepatic impairment. 66 Anotherevolocumab study reported no differences in LDL-C lowering or safety among patients with normal renal function and those with severe renalimpairmentorend-stagerenaldisease. 67 Therecentlypublished FOURIER study included patients with renal impairment (glomerular filtrationrateaslowas20mL/min) 26 and subgroup analyses examining the safety and efficacy of evolocumab in this population are expected.…”
Section: Safety Data For Anti-pcsk9 Antibodies and Other Lltsmentioning
confidence: 99%